Faktor-Faktor yang Mempengaruhi Tingkat Bagi Hasil Deposito Mudharabah pada Bank Umum Syariah selama Pandemi COVID-Periode 2019-2021 - Rosmelina, Helmi; Adetio Setiawan, Romi; Hariyadi, Rizky (Indonesian Journal of Islamic Economics and Business, 2024)
This study aims to analyze the factors influencing the profit-sharing level of mudharabah deposits in Islamic commercial banks both partially and simultaneously during the COVID-19 pandemic in Indonesia from 2019 to 2021. The dependent variable in this study is the profit-sharing rate of mudharabah deposits, while the independent variables include Financing to Deposits Ratio (FDR), Non-Performing Financing (NPF), and Inflation. The population comprises Islamic commercial banks operating in Indonesia that have published comprehensive financial reports during the vulnerable period from 2019 to 2021. Following the selection process, the target population consists of five banks, namely BCA Syariah Bank, Mega Syariah Bank, Panin Dubai Syariah Bank, Bukopin Syariah Bank, and Victoria Syariah Bank. The sampling method employed in this study is a nonprobability sampling technique using purposive sampling. The results indicate that both partially and simultaneously, the variables Financing to Deposits Ratio (FDR), Non-Performing Financing (NPF), and Inflation significantly affect the profit-sharing level of mudharabah deposits. The Coefficient of Determination (R2) reveals that in this study, all independent variables contribute to the dependent variable by 60.9%. The remaining 39.1% is influenced by other variables not included in this study, such as Capital Adequacy Ratio (CAR), interest rates, and other factors.